Humoral and T-Cell Immune Response After 3 Doses of Messenger RNA Severe Acute Respiratory Syndrome Coronavirus 2 Vaccines in Fragile Patients: The Italian VAX4FRAIL Study. (7th July 2022) - Corradini, Paolo; Agrati, Chiara; Apolone, Giovanni; Mantovani, Alberto; Giannarelli, Diana; Marasco, Vincenzo; Bordoni, Veronica; Sacchi, Alessandra; Matusali, Giulia; Salvarani, Carlo; Zinzani, Pier Luigi; Mantegazza, Renato; et al.
Abstract: Background: Patients with solid or hematological tumors or neurological and immune-inflammatory disorders are potentially fragile subjects at increased risk of experiencing severe coronavirus disease 2019 and an inadequate response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. Methods: We designed a prospective Italian multicenter study to assess humoral and T-cell responses to SARS-CoV-2 vaccination in patients (n = 378) with solid tumors (ST), hematological malignancies (HM), neurological disorders (ND), and immunorheumatological diseases (ID). A group of healthy controls was also included. We analyzed the immunogenicity of the primary vaccination schedule and booster dose. Results: The overall seroconversion rate in patients after 2 doses was 62.1%. Significantly lower rates were observed in HM (52.4%) and ID (51.9%) than in ST (95.6%) and ND (70.7%); a lower median antibody level was detected in HM and ID versus ST and ND ( P < .0001). Similar rates of patients with a positive SARS-CoV-2 T-cell response were found in all disease groups, with a higher level observed in ND. The booster dose improved the humoral response in all disease groups, although to a lesser extent in HM patients, whereas the T-cell response increased similarly in all groups. In the multivariable logistic model, independent predictors of seroconversion were disease subgroup, treatment type, and age. Ongoing treatment known to affect the immune system was associated with the worst humoral response to vaccination ( P < .0001) but had no effect on T-cell responses. Conclusions: Immunosuppressive treatment more than disease type per se is a risk factor for a low humoral response after vaccination. The booster dose can improve both humoral and T-cell responses. Abstract : Compared with healthy individuals, fragile patients have a lower rate of humoral and cellular response after primary vaccination schedule and booster dose. The type of immunosuppressive treatment has greater impact on humoral response than disease subtype, but it has a lower influence on T-cell response.